Efficient privacy preserving predicate encryption with fine-grained searchable capability for Cloud storage. (November 2016) - Wang, Xu An; Xhafa, Fatos; Cai, Weiyi; Ma, Jianfeng; Wei, Fushan
Highlights: We present an efficient predicate encryption system for the class of inner-product predicates that is fully secure without random oracles. PEFKS can not only test whether multiple keywords were present in the ciphertext, but also can evaluate the relations of the keywords, such as equal, disjunction/conjunction. We prove that IND-AH-CPA secure PE implies the existence of IND- PEFKS-CPA secure PEFKS, and develop a transformation of PE to PEFKS. The transformation is efficient. We also use it to construct a PEFKS scheme from our PE. We present a privacy preserving framework for implementing efficient predicate encryption with ne-grained searchable capability and roughly analysis its security. Graphical abstract: Abstract: With the fast development in Cloud storage technologies and ever increasing use of Cloud data centres, data privacy and confidentiality has become a must. Indeed, Cloud data centres store each time more sensitive data such as personal data, organizational and enterprise data, transactional data, etc. However, achieving confidentiality with flexible searchable capability is a challenging issue. In this article, we show how to construct an efficient predicate encryption with fine-grained searchable capability. Predicate Encryption ( PE ) can achieve more sophisticated and flexible functionality compared with traditional public key encryption. We propose an efficient predicate encryption scheme by utilizing the dual system encryption technique, which can also be proved to be IND-AH-CPA (indistinguishable under chosen plain-text attack for attribute-hiding) secure without random oracle. We also carefully analyse the relationship between predicate encryption and searchable encryption. To that end, we introduce a new notion of Public-Key Encryption with Fine-grained Keyword Search ( PEFKS ). Our results show that an IND-AH-CPA secure PE scheme can be used to construct an IND-PEFKS-CPA (indistinguishable under chosen plain-text attack for public-key encryption with fine-grained keyword search) secure PEFKS scheme. A new transformation of PE-to-PEFKS is also proposed and used to construct an efficient PEFKS scheme based on the transformation from the proposed PE scheme. Finally, we design a new framework for supporting privacy preserving predicate encryption with fine-grained searchable capability for Cloud storage. Compared to most prominent frameworks, our framework satisfies more features altogether and can serve as a basis for developing such frameworks for Cloud data centres.